Targeting, rhetoric and the failure of grassroots jihad - Ramsay, Gilbert (Journal of terrorism research, 2012)
In this paper I examine the apparent failure of Al Qaeda ideologues, not for want of trying, to incite a widespread campaign of ‘individual jihad’. Not only are instances of genuinely ‘leaderless’ jihadist violence rare, they also tend to be more discriminate and less lethal in their targeting than the operations which Al Qaeda expresses a discursive preference for, and which it attempts to carry out. I argue that an explanation for the rather constrained nature of grassroots jihadist violence can be found, rather paradoxically, in the logic of collective action, which seems to underlie the rhetorical attempts of jihadist ideologues to incite violence. I then briefly examine the possible implications of this for understanding what makes for a successful ‘leaderless’ terrorist campaign.Publisher PD